(untitled) (Revista Rupturas, 2021)
This article analyses how sexual and reproductive health has been constructed as a policy problem in Costa Rica´s Public Healthcare System, in the context of implementation of the Mesoamerica Initiative in Golfito region. It will be argued that adolescents are seen from the pathology and anormality -focusing on personal fails (their affectivity and identity) as well as socialization fails (relative to family and peer groups). As a result, their rights recognition is based on a negative stand. The study is qualitative -document analysis, as well as interviews and focus groups conducted to public healthcare officials.